2018
DOI: 10.1186/s12879-018-3055-3
|View full text |Cite
|
Sign up to set email alerts
|

Utility of posaconazole therapeutic drug monitoring and assessment of plasma concentration threshold for effective prophylaxis of invasive fungal infections: a meta-analysis with trial sequential analysis

Abstract: BackgroundPosaconazole therapeutic drug monitoring (TDM) is increasingly used in clinical practice. However, the utility of posaconazole TDM and the target of posaconazole plasma concentration for clinical successful prophylaxis remain uncertain and controversial. The aim of this study was to evaluate posaconazole exposure-response relationship and determine an optimum posaconazole concentration for prophylaxis against invasive fungal infections (IFIs).MethodsBibliographic databases were searched (from incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 58 publications
0
16
0
5
Order By: Relevance
“…A serum level of PCZ > 0.70 µg/ml is normally the target concentration for effective prophylaxis (Maleki et al, 2018). A meta-analysis of 28 studies that involved 1,930 patients found that patients with PCZ serum concentrations >0.5 mg/L were twice as likely to achieve successful responses compared to those with lower concentrations (Chen et al, 2018). In our study, a cutoff concentration value of 0.47 µg/ml is recommended, which provides a critical evaluating index for PCZ prophylaxis during the TDM process in China.…”
Section: Discussionmentioning
confidence: 99%
“…A serum level of PCZ > 0.70 µg/ml is normally the target concentration for effective prophylaxis (Maleki et al, 2018). A meta-analysis of 28 studies that involved 1,930 patients found that patients with PCZ serum concentrations >0.5 mg/L were twice as likely to achieve successful responses compared to those with lower concentrations (Chen et al, 2018). In our study, a cutoff concentration value of 0.47 µg/ml is recommended, which provides a critical evaluating index for PCZ prophylaxis during the TDM process in China.…”
Section: Discussionmentioning
confidence: 99%
“…Higher C min (> 0.5-0.7 mg/L) has been associated with reduced breakthrough infections in patients receiving posaconazole prophylaxis [143][144][145][146][147][148][149][150]. Patients with invasive aspergillosis demonstrated improved clinical response with an average posaconazole concentration of > 1 mg/L [151,152].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Thus, C min is also frequently used for TDM measures in practice and considered as a more conservative and practicable index [30,97]. A recent metaanalysis indicated that a C min of 0.5 mg/L could represent a clear margin separating successful from failed prophylaxis [98].…”
Section: Prophylaxismentioning
confidence: 99%